1999
DOI: 10.1038/15242
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and ionizing radiation enhance the growth of BCCs and trichoblastomas in patched heterozygous knockout mice

Abstract: Basal cell carcinomas, the commonest human skin cancers, consistently have abnormalities of the hedgehog signaling pathway and often have PTCH gene mutations. We report here that Ptch+/- mice develop primordial follicular neoplasms resembling human trichoblastomas, and that exposure to ultraviolet radiation or ionizing radiation results in an increase in the number and size of these tumors and a shift in their histologic features so that they more closely resemble human basal cell carcinoma. The mouse basal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
349
0
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(374 citation statements)
references
References 28 publications
16
349
0
9
Order By: Relevance
“…23 It was reported that PTCH þ /À mice have a higher incidence of squamous cell carcinomas after ultraviolet (UV) exposure, and the size of the tumor is also greatly increased. 24 Therefore, it is possible to postulate that genetic alteration or deregulation of the expression of PTCH superimposed with another genetic alteration such as UV exposure or p53 alteration by HPV may play a role in the development of squamous cell carcinoma of uterine cervix.…”
Section: Discussionmentioning
confidence: 99%
“…23 It was reported that PTCH þ /À mice have a higher incidence of squamous cell carcinomas after ultraviolet (UV) exposure, and the size of the tumor is also greatly increased. 24 Therefore, it is possible to postulate that genetic alteration or deregulation of the expression of PTCH superimposed with another genetic alteration such as UV exposure or p53 alteration by HPV may play a role in the development of squamous cell carcinoma of uterine cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Doxycycline (Dox)‐inducible GLI1‐expressing HaCaT keratinocytes and mouse BCC cell line ASZ00122 were grown as described previously 23, 24. Induction of GLI1 expression in HaCaT keratinocytes was done as reported in Refs.…”
Section: Methodsmentioning
confidence: 99%
“…Su(Fu) null mouse mutants not only fail to repress the pathway (Svard et al, 2006), but have some phenotypes similar to inactivation of Ptch1. Although Ptch1 þ /À mice are predisposed to developing medulloblastoma and rhabdomyosarcoma, and basal cell carcinomas following irradiation (Goodrich et al, 1997;Hahn et al, 1998;Aszterbaum et al, 1999b), Su(fu) þ /À mice mainly develop a skin phenotype characterized by basaloid epidermal proliferations. Moreover, Su(Fu) null MEFs and wild-type cells treated with Su(Fu) siRNAs display Hh pathway activation, supporting a central role in pathway repression (Svard et al, 2006).…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%